Anti-inflammatory and wound healing properties of lactic acid bacteria and its peptides - Saravanan, Parikhshith; R, Pooja; Balachander, Nanditaa; K, Kesav Ram Singh; S, Silpa; S, Rupachandra (Folia microbiologica, 2023)
Recent studies manifest an increase of inflammatory diseases at an alarming rate due to gut microbiota dysbiosis, genetic and other environmental factors. Lactic acid bacteria (LAB) are known for their antimicrobial properties and their extensive applications in food and pharmaceutical industries. Cyclic peptides are receiving increased attention due to their remarkable stability to withstand variations in temperature and pH. LAB produces anti-inflammatory that can inhibit lipopolysaccharide-induced production of proinflammatory cytokines in macrophages. The structural backbones of cyclic peptides offer a promising approach for the treatment of chronic inflammatory conditions. The current review aims to present the overview of anti-inflammatory and wound healing properties of LAB-derived cyclic peptides.
Keywords: Lactobacillales; Wound Healing; Peptides, Cyclic; Anti-Inflammatory Agents; antiflogistika; peptidy; cyklické peptidy; hojení ran; Peptides